1971
DOI: 10.1172/jci106635
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture studies of proximal tubule albumin concentrations in normal and nephrotic rats

Abstract: A B S T R A C T The concentration of serum albumin in proximal tubule fluid of normal rats and animals with aminonucleoside nephrosis was studied using renal micropuncture techniques. Albumin was quantitated by an ultramicrodisc electrophoresis method capable of measuring 3 X 10'" g of albumin, in 10 nl volumes. With this sensitivity., only small samples of tubule fluid were required for analysis. Collectifn times could be kept short, therefore decreasing the opportunity for sample contamination with extraneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
84
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 13 publications
7
84
0
1
Order By: Relevance
“…The relationship between the sclerosis index and albumin filtration rate, determined for each glomerulus in group IA rats, is demonstrated Our ELISA method detects < 1 ng/ml albumin and provides a slightly more sensitive assay system than the ultramicrodisc gel electrophoresis technique that has been used for the measurement of albumin in tubular fluid (27). In group 1 B rats, which were prepared in a fashion similar to that of group IA rats, we examined the population distribution ofglomeruli with varying degrees of sclerosis index, which were obtained from multiple thin section analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the sclerosis index and albumin filtration rate, determined for each glomerulus in group IA rats, is demonstrated Our ELISA method detects < 1 ng/ml albumin and provides a slightly more sensitive assay system than the ultramicrodisc gel electrophoresis technique that has been used for the measurement of albumin in tubular fluid (27). In group 1 B rats, which were prepared in a fashion similar to that of group IA rats, we examined the population distribution ofglomeruli with varying degrees of sclerosis index, which were obtained from multiple thin section analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, micropuncture studies revealed that albumin concentrations range from 20 to 30 g/ml in the proximal tubules of rodents. The induction of nephrosis causes up to a 100-fold increase in the albumin concentration prevailing in the proximal tubule (22,27). Therefore, a range of protein concentrations comparable to those used in other studies were chosen.…”
Section: Discussionmentioning
confidence: 99%
“…This process is probably responsible for the enormous variation in tubular lumen albumin concentrations depending on the method of collection. 1,20 Tojo and Endou 21 noted a 50-fold variation for serially collected fractions from the proximal tubular lumen and had to eliminate 75% of their data to obtain a sieving coefficient of 0.0006. In fact, the initial fractions collected indicate an albumin GSC comparable to that obtained by our 2-photon study, but these data were eliminated as it was thought to be the result of plasma contamination.…”
mentioning
confidence: 99%